MENGUNGKAP KECURANGAN (FRAUD) PEMBIAYAAN KREDIT PADA PT. BANK CENTRAL ASIA. TBK KCU PANAKKUKANG - Rahmawati. R Rahmawati. R (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
This research was conducted with the aim to know Fraud that happened in Credit Financing of PT. Bank Central Asia. Tbk. KCU Panakkukang.This research is Qualitative Research. The object of this research is PT. Bank Central Asia. Tbk. KCU Panakkukang by using interview and analysis method to COSO internal system with control system applied to bank financing.The results of this study indicate that (1) internal control system on Financing PT. Bank Central Asia, Tbk has been running well in accordance with applicable system but effective. (2) Ineffective internal control systems have a negative effect on the performance of employees who commit fraud.This means that internal control systems are indispensable for individuals and those with higher levels of tasks and responsibilities.